Salafism in Salatiga City: a Study of Those Who Fight in the Name of Islam 1990-2020 - Yufana, Aldy (Nur Science Institute, 2024)
Abstract The dynamics of life in the city of Salatiga, which is inhabited by people from various walks of life, have made it known as a plural city. Form such a diverse society, various thoughts and understandings of Islam were both, both from Muhammadiyah and Nahdlatul Ulama circles. However, in the last decade of the Soeharto government, a term emerged which was considered a new current of Islam from the Middle East, the became known as the Salafi Muslim group. The discourse and historical flow of Salafi development in Indonesia started form the establishment of the LIPIA campus in Jakarta in 1980 to the establishment of the Al-Irsyad Islamic Boarding School in Tengaran, Semarang Regency in 1987. By using historical methods, this research can find some interesting records such as entering the 1990s period which became a new dynamic of Islam in Salatiga City, because since the late 90s this group which is identical to pants above the ankles and has long beards began to mushroom in the heart of Salatiga city and surrounding areas. The results of this research include; (1) The initial history of the entry of the salafi community in the city of Salatiga, (2) The network of the salafi community in the city of Salatiga which formed a solidarity for the purpose of da’wah, (3) The development of the salafi community which began to preach through various media, including the media social. Keywords: salafi, islamic preaching, salatiga. REFERENCE Abdillah, A. D. (2022). Aktivisme Islam Salatiga dari Jejak Laskar Diponegoro sampai Pasca Kemerdekaan. Jurnal Ilmu Sejarah, 1-21. As-Sewed, M. U. (2014). Sejarah Dakwah Salafiyah di Indonesia. [M. U. As-Sewed, Pemain, & ilmusyari.com] Madiun, Jawa Timur, Indonesia. Aswar, H. (2016). Politik Luar Negeri Arab Saudi dan Ajaran Salafi-Wahabi di Indonesia. JISIERA : The Journal of Islamic Studies and International Relations, 15-30. Baisa, Y. U. (2023). EPS 1 Implementasi Pengasuhan Berbasis Fitrah Bersama Ustadz Yusuf Ba'isa, Lc. Bincang Pendidikan Islam. [Y. U. Baisa, Pemain, & P. I.-I. Tengaran] Semarang, Jawa Tengah, Indonesia. Basri, M. R. (2022). Gejala Hijrah di Indonesia : Transformasi dari Islamisme Fundamentalis Menuju Islamisme Populer. Jurnal Maarif, 31-51. Fatkhurrahman. (2024, Februari 19). Sejarah dan Perkembangan Dakwah Salafi di Kota Salatiga. (A. Yufana, Pewawancara) Hasan, N. (2008). Laskar Jihad, Islam, Militansi, dan Pencarian Identitas di Indonesia Pasca-Orde Baru. Jakarta: Pustaka LP3ES. Hidayat, D. (2012). Gerakan Dakwah Salafi di Indonesia pada Era Reformasi. Jurnal Sosiologi Masyarakat, 115-133. Krismono. (2017). Salafisme di Indonesia : Ideologi, Politik Negara, dan Fragmentasi. Jurnal Millah, 173-202. Loedoe Haga, C. S., Prianto, Y., & Arya Putra, M. R. (2022). Toleransi dalam Kehidupan Masyarakat di Kota Salatiga, Jawa Tengah. Jurnal Binamulia Hukum, 139-150. Miftahuddin. (2013). Krisis Identitas Kaum Hadrami : Sejarah Pergulatan Pergerakan Al-Irsyad Era Reformasi Indonesia. Yogyakarta: LPPM UNY. Shalihati, K. N. (2019). Islam Puritan dan Otorita Agama : Dakwah Radio Bass FM di Salatiga. Jurnal Dakwah Risalah, 168-182. Sidik, F. F. (2019). Mengkaji Ulang Sebagai Kota Toleransi : Masa Kolonial Hingga Pasca Kemerdekaan. Jurnal Al-Qalam, 457-466. Suaidi, A. A. (2024, Mei 14). Respons NU terhadap Salafi di Salatiga. (A. Yufana, Pewawancara) Wahid, D., & Makruf, J. (2017). Suara Salafisme : Radio Dakwah di Indonesia. Jakarta: Pusat Pengkajian Islam dan Masyarakat (PPIM UIN Syarif Hidayatullah Jakarta dan Prenadamedia Group. Zainuddin, A. (2024, Maret 8). Sejarah Radio Bass FM dan Dakwah Salafi di Salatiga. (A. Yufana, Pewawancara) Zumrotun, S., Islamiyah, D., & Mahmud, M. R. (2010). Menabur Benih Islam Salafi di Pedesaan (Studi Etnografi di Kelurahan Tingkir Lor Kota Salatiga dan Desa Tegalwaton Kabupaten Semarang). Salatiga: P3M.